2020
DOI: 10.1002/aqc.3367
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Guiana dolphin (Sotalia guianensis) in southeast of Brazil: Driven by prey distribution or human fishing activity?

Abstract: 1. This study used models to assess how the type of prey caught by artisanal fishermen influenced the occurrence of Guiana dolphins (Sotalia guianensis) in the region of the estuarine lagunar comple.x of Cananéia (São Paulo, Brazil). 2. The data were collected from January 2012 to November 2014, during three fieldwork expeditions per season (spring, summer, autumn, winter). 3. Mullets (Mugil liza) were the fish with the highest association to dolphins, followed by Oligoplites spp. and Lobotes spp.; Mugil curem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
1
3
0
1
Order By: Relevance
“…A previous study suggested a high abundance of Guiana dolphins in the SP, primarily occupying interior bays and channel systems for feeding, and mainly interacting with traditional fishing gear known as ‘curral’ in this area (see Torres & Beasley, 2003). This fishing gear does not appear to pose a threat to Guiana dolphins, and a similar interaction has been reported in other regions of Brazil (Ferro de Godoy et al, 2020; Monteiro‐Filho, 1995). However, population information for more open coastal areas along the Amazon Atlantic coast is lacking, necessitating further studies to confirm this supposition.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…A previous study suggested a high abundance of Guiana dolphins in the SP, primarily occupying interior bays and channel systems for feeding, and mainly interacting with traditional fishing gear known as ‘curral’ in this area (see Torres & Beasley, 2003). This fishing gear does not appear to pose a threat to Guiana dolphins, and a similar interaction has been reported in other regions of Brazil (Ferro de Godoy et al, 2020; Monteiro‐Filho, 1995). However, population information for more open coastal areas along the Amazon Atlantic coast is lacking, necessitating further studies to confirm this supposition.…”
Section: Discussionsupporting
confidence: 80%
“…In the dry season, the drought within the bay allows marine waters to enter, increasing the probability of strandings in the inner areas of the MB. Habitat use and changes in preferential areas driven by shifts in the abundance of major prey, seasonal salinity gradient and foraging strategies have been previously indicated for populations of Guiana dolphins from Eastern and Southern Brazil (Ferro de Godoy et al, 2020;Rodrigues et al, 2020;Wedekin et al, 2010).…”
Section: Seasonalitymentioning
confidence: 95%
“…A baixa variação no número de indivíduos nos grupos também foi observada (SANTOS; ROSSO, 2007). Outros dados apontaram a relação positiva da presença do boto-cinza e os cercos fixos e negativa com as redes de emalhe (GODOY et al, 2020).…”
Section: Sotalia Guianensis Boto-cinza E Pontoporia Blainvillei Toninhaunclassified
“…Between 1997 and 2021, 164 publications documented the scale of marine mammal bycatch, including fishery and gear-specific bycatch estimates (Julian and Beeson, 1998;Allen, 2000;D'Agrosa et al, 2000;Ortega-Argueta et al, 2005). Marine mammal bycatch is spatially variable, with larger bycatch estimates coinciding with areas of higher marine mammals or fish (prey species) abundance (Lewison et al, 2004(Lewison et al, , 2014de Godoy et al, 2020;Baird et al, 2021), reflecting the increasing resource overlap between marine mammals and fishery operations. In many regions, spatial, temporal, and oceanographic factors affect bycatch.…”
Section: Direct Interactions: Bycatchmentioning
confidence: 99%